2016
DOI: 10.1097/gme.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and sexual function of naturally postmenopausal women on an ultralow-concentration estriol vaginal gel

Abstract: Estriol vaginal gel (0.005%) therapy significantly improves the trophism of the vaginal mucosa and the sexual health and QoL of naturally postmenopausal women. These results confirm that low doses of vaginal estrogen must be considered as the first choice for the initial treatment of postmenopausal genitourinary symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…Various therapeutic strategies, hormonal or not, oral or local, have been proposed for improving the vaginal microflora of postmenopausal women. Hormonal therapy (oral or local) has been associated with a healthy vaginal microbiota that is achieved by repopulating the Lactobacillus species back to a premenopausal status and by reducing the pH of vaginal fluid ( 11 - 13 ). Additionally, the use of vaginal estrogens reduced the incidence of urinary infections in postmenopausal women ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various therapeutic strategies, hormonal or not, oral or local, have been proposed for improving the vaginal microflora of postmenopausal women. Hormonal therapy (oral or local) has been associated with a healthy vaginal microbiota that is achieved by repopulating the Lactobacillus species back to a premenopausal status and by reducing the pH of vaginal fluid ( 11 - 13 ). Additionally, the use of vaginal estrogens reduced the incidence of urinary infections in postmenopausal women ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…There were several studies demonstrated beneficial effects of estrogens, specifically designed to be administered vaginally, on female sexual function and quality of life [42,43]. This study was designed to be a pioneer of using oral medication, off-labelly administered vaginally to treat FSD.…”
Section: Discussionmentioning
confidence: 99%
“…Brand names include Ovestin ® and Gynest ® . A low-dose estriol vaginal gel formulation (0.005% estriol vaginal gel) has been shown to significantly increase vaginal maturation index and improve vaginal pH compared with a baseline evaluation in postmenopausal women [70]. A combination of low-dose estriol and lyophilized viable Lactobacillus acidophilus tablet appears effective for relieving GSM symptoms, reducing urogenital atrophy, and restoring vaginal flora [71].…”
Section: Available Treatmentsmentioning
confidence: 99%